The Role of Business Management, Government Support, and Business Networks in the Sustainability of Culinary Micro, Small, and Medium Enterprises (MSMEs) in Serdang Bedagai Regency - Khairul Faiz Batubara; Yenni Samri Juliati Nasution; Yusrizal Yusrizal (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of business management, government support, and business networks on the sustainability of culinary micro and small enterprises (MSEs) in Serdang Bedagai Regency. The background of this study is based on the importance of the MSE sector in supporting the regional economy, but many business actors still face obstacles in terms of management, access to government support, and minimal business networks. This study uses a quantitative approach with an associative method and multiple linear regression analysis techniques. Data collection was carried out through questionnaires to 100 culinary MSE respondents selected using purposive sampling techniques. The results of the study show that partially, business management, government support, and business networks have a positive and significant effect on MSE sustainability. Simultaneously, the three variables contribute 97.1% to business sustainability. The business management variable is the most dominant factor in influencing MSE sustainability. This finding strengthens the theory of strategic management and sustainability, and is in line with several previous studies that emphasize the importance of managerial aspects, institutional support, and network collaboration in maintaining the existence of MSEs. This research provides important implications for business actors, local governments, and related parties in designing integrated strategies to strengthen the sustainability of culinary MSMEs in a sustainable manner.